2022
DOI: 10.1111/dmcn.15171
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of bulbar function in spinal muscular atrophy type 1 treated with nusinersen

Abstract: To assess the evolution of bulbar function in nusinersen-treated spinal muscular atrophy type 1 (SMA1).Method: This single-centre retrospective study identified 24 patients (14 females and 10 males) with SMA1, treated with nusinersen between 2017 and 2020. We adapted and validated the Paediatric Functional Oral Intake Scale (p-FOIS), which is an outcome measure to assess bulbar function. Analysis considered SMA1 subtype, nutritional support, and Children's Hospital of Philadelphia Infant Test of Neuromuscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
(81 reference statements)
3
25
0
Order By: Relevance
“…It is worth noting, however, that 14.6% of patients required GT due to an expectation of additional gains, especially concerning bulbar function. This data is in line with other published studies that have suggested that bulbar dysfunction has a less satisfactory response than the motor response in those patients treated with nusinersen [28,29]. At the end of follow-up in our study, the number of SMA type 1 patients on an oral diet increased from 15 (45.4%) to 18 (54.5%), an improvement also found in other real-life studies that used GT after prior use of nusinersen [30].…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting, however, that 14.6% of patients required GT due to an expectation of additional gains, especially concerning bulbar function. This data is in line with other published studies that have suggested that bulbar dysfunction has a less satisfactory response than the motor response in those patients treated with nusinersen [28,29]. At the end of follow-up in our study, the number of SMA type 1 patients on an oral diet increased from 15 (45.4%) to 18 (54.5%), an improvement also found in other real-life studies that used GT after prior use of nusinersen [30].…”
Section: Discussionsupporting
confidence: 93%
“…The FEES protocol described provides valuable information about the unique features. The few clinical tools already used in children with type 1 SMA [ 3 , 9 , 21 ] offer an initial basis, but in their current form, they are not suitable for future studies to make an adequate statement on swallowing status and development. Systematic test development and focus studies on this topic are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, the children can never sit, mostly die within the first 2 years of life, or become dependent on supportive ventilation [ 8 ]. Due to the rapid death of motor neurons, complete loss of swallowing function is possible within a few weeks, requiring close monitoring of swallowing ability [ 1 , 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Penetration-Aspiration Scale (P-A score) was used for ratings of penetration and aspiration, and the Pediatric Functional Oral Intake Scale (P-FOIS) was used to measure current dietary intake. 3,8…”
Section: Methodsmentioning
confidence: 99%